Analisis Pengendalian Kualitas Pelapisan Baja Material Siku SS540 di PT. X dengan Menggunakan Metode SPC - Dewi, Aprilia Puspita; Rachmadita, Renanda Nia; Rachman, Farizi (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
Quality is an important factor for people in selecting and enjoying a product or service in addition to competitive prices. Therefore, for companies to survive and maintain its existence, it is required to remain continuously maintain and improve the quality of the products or services they offer. PT. X is a company engaged in the steel plating with Hot Dip Galvanize method. In the implementation of quality control in PT. X, after analysis on coating processes steel material elbow 50 x 50 x 5 (mm) in length 2000 mm Type SS540 processed vertically in the period January - December 2014. By using SPC method, that is especially by calculation using the map control x̅, R and S is still a point of being out of control that indicates the thickness of the coating out of provisions. However, the number of points out of the control limits is still relatively small. However, PT. X must remain continuously maintain and improve the quality of their products and services by taking into account four factors that influence the final armor plating that is the human factor, the factor labor process, machine factors and material factor.